A low-loss and high-permeability soft ferrite core and a manufacturing method thereof
Patent Information
- Application Number
- CN202410878020.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-02
AI Technical Summary
[0003]为了克服上述的技术问题,本发明的目的在于提供一种低损耗高磁导率的软磁铁氧体磁芯及其制造方法:通过将Fe2O3、MnO、ZnO、VO、S iO2、CaCO3、性能增强剂以及无水乙醇加入至球磨机中球磨,得到球磨浆料,将球磨浆料放置于真空干燥箱中干燥,之后粉碎过筛,之后加入至压力机中压制成型,得到磁芯生坯,将磁芯生坯放置于管式炉中烧结,之后随炉冷却,经过打磨、清洗去除表面杂质和毛刺后,得到低损耗高磁导率的软磁铁氧体磁芯,解决了传统的软磁铁氧体磁芯的损耗大,磁导率不佳的问题
[0026]本发明的一种低损耗高磁导率的软磁铁氧体磁芯及其制造方法,通过将Fe2O3、MnO、ZnO、VO、S i O2、CaCO3、性能增强剂以及无水乙醇加入至球磨机中球磨,得到球磨浆料,将球磨浆料放置于真空干燥箱中干燥,之后粉碎过筛,之后加入至压力机中压制成型,得到磁芯生坯,将磁芯生坯放置于管式炉中烧结,之后随炉冷却,经过打磨、清洗去除表面杂质和毛刺后,得到低损耗高磁导率的软磁铁氧体磁芯;该软磁铁氧体磁芯由于特定的元素配比和制造工艺,磁芯在高频应用中的损耗显著降低,优化的元素配比和烧结工艺保证了磁芯具有较高的磁导率,能够满足各种电子器件对磁导率的需求,而且该制造方法简单、高效,适合大规模生产。
Smart Images

Figure BDA0004923682300000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnetic materials, and in particular to a low-loss and high-permeability soft ferrite core and a manufacturing method thereof. Background Art
[0002] With the rapid development of electronic technology, the requirements for magnetic materials are getting higher and higher. As a key component in electronic devices, the magnetic permeability and loss characteristics of soft ferrite cores directly affect the performance of electronic devices. At present, although there are many soft ferrite cores on the market, their losses are still large under high-frequency conditions, and their magnetic permeability needs to be improved, which limits their application in high-performance electronic devices. Therefore, the development of a low-loss and high-permeability soft ferrite core and its manufacturing method has important practical application value. Summary of the invention
[0003] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a low-loss and high-permeability soft ferrite core and a method for manufacturing the same: by adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, a performance enhancer and anhydrous ethanol into a ball mill and milling to obtain a ball-milled slurry, placing the ball-milled slurry in a vacuum drying oven for drying, then crushing and sieving, and then adding it to a press for compression molding to obtain a core green body, placing the core green body in a tubular furnace for sintering, and then cooling it with the furnace. After grinding and cleaning to remove surface impurities and burrs, a low-loss and high-permeability soft ferrite core is obtained, which solves the problems of high loss and poor permeability of traditional soft ferrite cores.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A low-loss and high-permeability soft ferrite core comprises the following components in parts by weight:
[0006] Fe2O3 51-59 parts, MnO 34-42 parts, ZnO 10-18 parts, VO 0.02-0.07 parts, SiO2 0.0012-0.0026 parts, CaCO3 0.03-0.07 parts, performance enhancer 0.1-3.9 parts and anhydrous ethanol 150-250 parts;
[0007] The performance enhancer is prepared by the following steps:
[0008] Step A1: Add nitrobenzene and benzene to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of -10-0°C and a stirring rate of 400-500r / min, then add dibromohydantoin solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, continue to stir and react for 1-2 hours, then continue to stir and react for 8-10 hours under the condition of heating to 45-50°C. After the reaction is completed, cool the reaction product to room temperature, then add it to distilled water, and then extract it with dichloromethane for 2-3 times, combine the extracts and dry the extracts with anhydrous sodium sulfate, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate product A;
[0009] Step A2: add the intermediate product A, 10% palladium carbon and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, introduce hydrogen to maintain the pressure at 0.8-0.9 MPa, then stir the reaction at a temperature of 60-65° C. and a stirring rate of 400-500 r / min for 8-10 hours, and after the reaction is completed, cool the reaction product to room temperature, and then vacuum filter, extract the filtrate with dichloromethane 2-3 times, combine the extracts and rotary evaporate the extracts to remove the solvent to obtain the intermediate product B;
[0010] Step A3: adding the intermediate product B, p-divinylbenzene and anhydrous ether into a three-necked flask equipped with a stirrer and a thermometer, introducing nitrogen protection, stirring the reaction at a temperature of -10-0°C and a stirring rate of 400-500r / min for 20-30min, then heating to 55-60°C and continuing to stir the reaction for 5-6h, cooling the reaction product to room temperature after the reaction, then rotary evaporating to remove the solvent, and then recrystallizing with petroleum ether to obtain an intermediate product C;
[0011] Step A4: Add the intermediate product C, triethanolamine, anhydrous potassium carbonate and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 15-20 minutes at a temperature of 25-30°C and a stirring rate of 400-500r / min, then raise the temperature to 90-95°C and continue stirring the reaction for 4-5 hours. After the reaction is completed, the reaction product is cooled to room temperature, poured into distilled water, and then allowed to stand, the organic phase is rotary evaporated to remove the solvent, and then recrystallized from ethyl acetate to obtain a performance enhancer.
[0012] As a further solution of the present invention: the usage ratio of the nitrobenzene, benzene and dibromohydantoin solution in step A1 is 10 mmol: 30-35 mL: 20-25 mL.
[0013] As a further solution of the present invention: the dibromohydantoin solution in step A2 is a solution formed by dissolving dibromohydantoin in benzene at a ratio of 5 mmol: 8-10 mL.
[0014] As a further solution of the present invention: the usage ratio of the intermediate product A, 10% palladium carbon and anhydrous ethanol in step A2 is 3g: 0.05-0.09g: 50-55mL.
[0015] As a further solution of the present invention: the usage ratio of the intermediate product B, p-divinylbenzene and anhydrous ether in step A3 is 22-25 mmol: 10 mmol: 80-100 mL.
[0016] As a further scheme of the present invention: the usage ratio of the intermediate product C, triethanolamine, anhydrous potassium carbonate and N,N-dimethylformamide in step A4 is 10 mmol: 60-70 mmol: 80-90 mmol: 120-150 mL.
[0017] As a further solution of the present invention: a method for manufacturing a low-loss and high-permeability soft ferrite core comprises the following steps:
[0018] Step 1: Weigh 51-59 parts of Fe2O3, 34-42 parts of MnO, 10-18 parts of ZnO, 0.02-0.07 parts of VO, 0.0012-0.0026 parts of SiO2, 0.03-0.07 parts of CaCO3, 0.1-3.9 parts of performance enhancer and 150-250 parts of anhydrous ethanol according to weight parts, and set aside;
[0019] Step 2: adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, performance enhancer and anhydrous ethanol into a ball mill for ball milling to obtain ball milling slurry;
[0020] Step 3: placing the ball mill slurry in a vacuum drying oven to dry, then crushing and sieving, and then adding it to a press to press and form, to obtain a magnetic core green body;
[0021] Step 4: Place the core green body in a tubular furnace for sintering, then cool it with the furnace, and after grinding and cleaning to remove surface impurities and burrs, a low-loss and high-permeability soft ferrite core is obtained.
[0022] As a further solution of the present invention: the ball milling conditions in step 2 are as follows: the ball milling rate is 400-500r / min, and the ball milling time is 10-20h.
[0023] As a further solution of the present invention: the drying conditions in step three are as follows: the temperature is 60-80°C, and the drying time is 3-5h; the pressing condition is a pressing pressure of 200-300MPa.
[0024] As a further solution of the present invention: the sintering conditions in step 4 are as follows: air environment, sintering temperature is 800-1200° C., and sintering time is 3-5 hours.
[0025] Beneficial effects of the present invention:
[0026] The invention discloses a low-loss and high-permeability soft ferrite core and a manufacturing method thereof. The method comprises the following steps: adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, a performance enhancer and anhydrous ethanol to a ball mill for ball milling to obtain ball milling slurry, placing the ball milling slurry in a vacuum drying oven for drying, crushing and screening the ball milling slurry, and then adding the ball milling slurry to a press for compression molding to obtain a magnetic core green body, placing the magnetic core green body in a tubular furnace for sintering, and then cooling the green body with the furnace, and grinding and cleaning to remove surface impurities and burrs to obtain a low-loss and high-permeability soft ferrite core. Due to a specific element ratio and manufacturing process, the loss of the soft ferrite core in high-frequency applications is significantly reduced, the optimized element ratio and sintering process ensure that the magnetic core has a high permeability, and can meet the requirements of various electronic devices for permeability. Moreover, the manufacturing method is simple and efficient and is suitable for large-scale production.
[0027] In the process of preparing the soft ferrite core, a performance enhancer is first prepared. First, nitrobenzene and dibromohydantoin are reacted. Dibromohydantoin is used as a brominating agent to brominate nitrobenzene, and bromine atoms are introduced into the benzene ring of nitrobenzene to obtain an intermediate product A. Then, the intermediate product A reacts with hydrogen. The hydrogen reduces the nitro group on the intermediate product A to an amino group to obtain an intermediate product B. Then, the intermediate product B reacts with p-divinylbenzene. The amino group on the intermediate product B reacts with the alkenyl group on the p-divinylbenzene to undergo a Michael addition reaction, thereby connecting in sequence to form a network structure to form an intermediate product C containing a large number of bromine atoms. Finally, the intermediate product C reacts with triethanolamine. The bromine atoms on the intermediate product C react with the hydroxyl groups on the triethanolamine, thereby introducing a large number of alcoholic hydroxyl groups. A performance enhancer is obtained; the molecular structure of the performance enhancer contains a large number of alcohol hydroxyl groups, which give the performance enhancer a lower surface tension and a higher surface activity, so that it is easy to adsorb on the surface of particles of each component of the soft ferrite core during the ball milling process to form a wrapping film, so that the surface reaches a saturated state, and no longer attracts each other and sticks into agglomerates, thereby improving the particle fluidity of each component, thereby facilitating the expansion of cracks, increasing the fragility of the particles of each component, and finally improving the ball milling effect and ball milling efficiency, thereby enabling the particles of each component to be fully refined and evenly doped with each other, and finally making the formed soft ferrite core internally tightly connected, thereby improving various properties of the soft ferrite core, and making the soft ferrite core have the advantages of low loss and high magnetic permeability. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] This embodiment is a method for manufacturing a low-loss and high-permeability soft ferrite core, comprising the following steps:
[0031] Step S1: 10 mmol nitrobenzene and 30 mL benzene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen protection is introduced. The mixture is stirred and reacted for 20 min at a temperature of -10°C and a stirring rate of 400 r / min. Then, 20 mL of dibromohydantoin solution formed by dissolving 5 mmol : 8 mL of dibromohydantoin in benzene is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the stirring reaction is continued for 1 h, and then the stirring reaction is continued for 8 h under the condition of heating to 45°C. After the reaction is completed, the reaction product is cooled to room temperature, and then added to distilled water, and then extracted twice with dichloromethane, the extracts are combined and dried over anhydrous sodium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain an intermediate product A;
[0032] Step S2: 3 g of intermediate product A, 0.05 g of 10% palladium carbon and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and hydrogen was introduced to maintain the pressure at 0.8 MPa, and then stirred for 8 hours at a temperature of 60° C. and a stirring rate of 400 r / min. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was extracted twice with dichloromethane, the extracts were combined and the extracts were rotary evaporated to remove the solvent to obtain intermediate product B;
[0033] Step S3: 22 mmol of intermediate product B, 10 mmol of p-divinylbenzene and 80 mL of anhydrous ether were added to a three-necked flask equipped with a stirrer and a thermometer, and nitrogen was introduced for protection. The mixture was stirred at a temperature of -10°C and a stirring rate of 400 r / min for 20 min, and then the mixture was heated to 55°C and stirred for 5 h. After the reaction, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation, and then recrystallized from petroleum ether to obtain intermediate product C;
[0034] Step S4: 10 mmol of intermediate product C, 60 mmol of triethanolamine, 80 mmol of anhydrous potassium carbonate and 120 mL of N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 15 min, and then the mixture is heated to 90° C. and stirred for reaction for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, poured into distilled water, and then allowed to stand. The organic phase is rotary evaporated to remove the solvent, and then recrystallized from ethyl acetate to obtain a performance enhancer;
[0035] Step S5: weigh 51 parts of Fe2O3, 34 parts of MnO, 10 parts of ZnO, 0.02 parts of VO, 0.0012 parts of SiO2, 0.03 parts of CaCO3, 0.1 parts of performance enhancer and 150 parts of anhydrous ethanol according to weight parts for later use;
[0036] Step S6: adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, performance enhancer and anhydrous ethanol into a ball mill, and ball milling for 10 hours at a ball milling rate of 400 r / min to obtain a ball milled slurry;
[0037] Step S7: placing the ball mill slurry in a vacuum drying oven, drying it at 60°C for 3 hours, then crushing it through a 100-mesh sieve, adding it to a press, and pressing it at a pressing pressure of 200 MPa to obtain a magnetic core green body;
[0038] Step S8: placing the core green body in a tubular furnace, sintering it in an air environment at a sintering temperature of 800°C for 3 hours, then cooling it in the furnace, and grinding and cleaning to remove surface impurities and burrs to obtain a low-loss and high-permeability soft ferrite core.
[0039] Embodiment 2:
[0040] This embodiment is a method for manufacturing a low-loss and high-permeability soft ferrite core, comprising the following steps:
[0041] Step S1: 10 mmol nitrobenzene and 32 mL benzene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction for 25 min at a temperature of -5°C and a stirring rate of 450 r / min, and then 22 mL of dibromohydantoin solution formed by dissolving 5 mmol : 9 mL of dibromohydantoin in benzene is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the addition is completed, the reaction is continued to be stirred for 1.5 h, and then the temperature is raised to 48°C and the reaction is continued to be stirred for 9 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to distilled water, and then extracted twice with dichloromethane, the extracts are combined and dried over anhydrous sodium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain an intermediate product A;
[0042] Step S2: 3 g of intermediate product A, 0.07 g of 10% palladium carbon and 52 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and hydrogen was introduced to maintain the pressure at 0.85 MPa, and then the reaction was stirred at a temperature of 62° C. and a stirring rate of 450 r / min for 9 hours. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was extracted twice with dichloromethane, the extracts were combined and the extracts were rotary evaporated to remove the solvent to obtain intermediate product B;
[0043] Step S3: 24 mmol of intermediate product B, 10 mmol of p-divinylbenzene and 90 mL of anhydrous ether were added to a three-necked flask equipped with a stirrer and a thermometer, and nitrogen was introduced for protection. The mixture was stirred at a temperature of -5°C and a stirring rate of 450 r / min for 25 min, and then the mixture was heated to 58°C and stirred for 5.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation, and then recrystallized from petroleum ether to obtain intermediate product C;
[0044] Step S4: 10 mmol of intermediate product C, 65 mmol of triethanolamine, 85 mmol of anhydrous potassium carbonate and 135 mL of N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 450 r / min for 18 min, and then the mixture is heated to 92° C. and stirred for reaction for 4.5 h. After the reaction is completed, the reaction product is cooled to room temperature, poured into distilled water, and then allowed to stand. The organic phase is rotary evaporated to remove the solvent, and then recrystallized from ethyl acetate to obtain a performance enhancer;
[0045] Step S5: weigh 55 parts of Fe2O3, 38 parts of MnO, 14 parts of ZnO, 0.05 parts of VO, 0.0018 parts of SiO2, 0.05 parts of CaCO3, 2.0 parts of performance enhancer and 200 parts of anhydrous ethanol according to weight parts for later use;
[0046] Step S6: adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, performance enhancer and anhydrous ethanol into a ball mill, and ball milling for 15 hours at a ball milling rate of 450 r / min to obtain a ball milled slurry;
[0047] Step S7: placing the ball mill slurry in a vacuum drying oven, drying it at 70°C for 4 hours, then crushing it through a 150-mesh sieve, and then adding it to a press, pressing it at a pressing pressure of 250 MPa to obtain a magnetic core green body;
[0048] Step S8: placing the core green body in a tubular furnace, sintering it in an air environment at a sintering temperature of 1000°C for 4 hours, then cooling it in the furnace, and grinding and cleaning to remove surface impurities and burrs to obtain a soft ferrite core with low loss and high magnetic permeability.
[0049] Embodiment 3:
[0050] This embodiment is a method for manufacturing a low-loss and high-permeability soft ferrite core, comprising the following steps:
[0051] Step S1: 10 mmol nitrobenzene and 35 mL benzene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen protection is introduced. The mixture is stirred for reaction at a temperature of 0° C. and a stirring rate of 500 r / min for 30 min, and then 25 mL of dibromohydantoin is added dropwise while stirring. The dibromohydantoin solution formed by dissolving 5 mmol : 10 mL of dibromohydantoin in benzene is added dropwise, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the stirring reaction is continued for 2 h, and then the temperature is raised to 50° C. and the stirring reaction is continued for 10 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to distilled water, and then extracted with dichloromethane for 3 times, the extracts are combined and dried over anhydrous sodium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain an intermediate product A;
[0052] Step S2: 3 g of intermediate product A, 0.09 g of 10% palladium carbon and 55 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and hydrogen was introduced to maintain the pressure at 0.9 MPa, and then the reaction was stirred for 10 hours at a temperature of 65° C. and a stirring rate of 500 r / min. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was extracted with dichloromethane for 3 times, the extracts were combined and the extracts were rotary evaporated to remove the solvent to obtain intermediate product B;
[0053] Step S3: 25 mmol of intermediate product B, 10 mmol of p-divinylbenzene and 100 mL of anhydrous ether were added to a three-necked flask equipped with a stirrer and a thermometer, and nitrogen was introduced for protection. The mixture was stirred at 0°C and a stirring rate of 500 r / min for 30 min, and then the mixture was heated to 60°C and stirred for 6 h. After the reaction, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation, and then recrystallized from petroleum ether to obtain intermediate product C;
[0054] Step S4: 10 mmol of intermediate product C, 70 mmol of triethanolamine, 90 mmol of anhydrous potassium carbonate and 150 mL of N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 500 r / min for 20 min, and then the mixture is heated to 95° C. and stirred for reaction for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, poured into distilled water, and then allowed to stand. The organic phase is rotary evaporated to remove the solvent, and then recrystallized from ethyl acetate to obtain a performance enhancer;
[0055] Step S5: weigh 59 parts of Fe2O3, 42 parts of MnO, 18 parts of ZnO, 0.07 parts of VO, 0.0026 parts of SiO2, 0.07 parts of CaCO3, 3.9 parts of performance enhancer and 250 parts of anhydrous ethanol according to weight parts for later use;
[0056] Step S6: adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, performance enhancer and anhydrous ethanol into a ball mill, and ball milling for 20 hours at a ball milling rate of 500 r / min to obtain a ball milled slurry;
[0057] Step S7: placing the ball mill slurry in a vacuum drying oven, drying it at 80°C for 5 hours, then crushing it through a 200-mesh sieve, adding it to a press, and pressing it at a pressing pressure of 300 MPa to obtain a magnetic core green body;
[0058] Step S8: placing the core green body in a tubular furnace, sintering it in an air environment at a sintering temperature of 1200°C for 5 hours, then cooling it in the furnace, and grinding and cleaning to remove surface impurities and burrs to obtain a low-loss and high-permeability soft ferrite core.
[0059] Comparative Example 1:
[0060] This comparative example is a method for manufacturing a low-loss and high-permeability soft ferrite core, comprising the following steps:
[0061] Step S1: weigh 59 parts of Fe2O3, 42 parts of MnO, 18 parts of ZnO, 0.07 parts of VO, 0.0026 parts of SiO2, 0.07 parts of CaCO3 and 250 parts of anhydrous ethanol according to weight parts for later use;
[0062] Step S2: adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3 and anhydrous ethanol into a ball mill, and ball milling for 20 hours at a ball milling rate of 500 r / min to obtain a ball milled slurry;
[0063] Step S3: placing the ball mill slurry in a vacuum drying oven, drying it at 80°C for 5 hours, then crushing it through a 200-mesh sieve, adding it to a press, and pressing it at a pressing pressure of 300 MPa to obtain a magnetic core green body;
[0064] Step S4: placing the core green body in a tubular furnace, sintering it in an air environment at a sintering temperature of 1200°C for 5 hours, then cooling it in the furnace, and grinding and cleaning to remove surface impurities and burrs to obtain a low-loss and high-permeability soft ferrite core.
[0065] Comparative Example 2:
[0066] This comparative example is a method for manufacturing a low-loss and high-permeability soft ferrite core, comprising the following steps:
[0067] Step S1: weigh 59 parts of Fe2O3, 42 parts of MnO, 18 parts of ZnO, 0.07 parts of VO, 0.0026 parts of SiO2, 0.07 parts of CaCO3, 3.9 parts of triethanolamine and 250 parts of anhydrous ethanol according to weight parts, and set aside;
[0068] Step S2: adding Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, triethanolamine and anhydrous ethanol into a ball mill, and ball milling for 20 hours at a ball milling rate of 500 r / min to obtain a ball milled slurry;
[0069] Step S3: placing the ball mill slurry in a vacuum drying oven, drying it at 80°C for 5 hours, then crushing it through a 200-mesh sieve, adding it to a press, and pressing it at a pressing pressure of 300 MPa to obtain a magnetic core green body;
[0070] Step S4: placing the core green body in a tubular furnace, sintering it in an air environment at a sintering temperature of 1200°C for 5 hours, then cooling it in the furnace, and grinding and cleaning to remove surface impurities and burrs to obtain a low-loss and high-permeability soft ferrite core.
[0071] The performance of the low-loss and high-permeability soft ferrite cores of Examples 1-3 and Comparative Examples 1-2 was tested, and the test results are as follows:
[0072]
[0073] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-2, the soft ferrite core of the present invention has the advantages of low loss and high magnetic permeability, wherein the addition of triethanolamine and a performance enhancer has an improvement effect on the performance of the soft ferrite core.
[0074] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0075] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A low-loss and high-permeability soft ferrite core, characterized in that: It comprises the following components in parts by weight: Fe2O3 51-59 parts, MnO 34-42 parts, ZnO 10-18 parts, VO 0.02-0.07 parts, SiO2 0.0012-0.0026 parts, CaCO3 0.03-0.07 parts, performance enhancer 0.1-3.9 parts and anhydrous ethanol 150-250 parts; The performance enhancer is prepared by the following steps: Step A1: stirring nitrobenzene and benzene for reaction, then adding dibromohydantoin solution dropwise while stirring, continuing stirring for reaction after the addition is complete, cooling the reaction product after the reaction is complete, then adding it into distilled water, then extracting, drying the extract, then vacuum filtering, and rotary evaporating the filtrate to obtain intermediate product A; Step A2: add intermediate product A, 10% palladium carbon and anhydrous ethanol into a three-necked flask, introduce hydrogen gas to react with stirring, cool the reaction product after the reaction is completed, then vacuum filter, extract the filtrate, and rotary evaporate the extract to obtain intermediate product B; Step A3: stirring the intermediate product B, p-divinylbenzene and anhydrous ether for reaction, cooling the reaction product after the reaction is completed, and then rotary evaporating and recrystallizing to obtain the intermediate product C; Step A4: Stir the intermediate product C, triethanolamine, anhydrous potassium carbonate and N,N-dimethylformamide for reaction. After the reaction is completed, cool the reaction product, pour it into distilled water, let it stand, rotary evaporate the organic phase, and then recrystallize to obtain a performance enhancer.
2. A low-loss and high-permeability soft ferrite core according to claim 1, characterized in that: The usage ratio of the nitrobenzene, benzene and dibromohydantoin solution in step A1 is 10 mmol: 30-35 mL: 20-25 mL.
3. The low-loss and high-permeability soft ferrite core according to claim 1, characterized in that: The dibromohydantoin solution in step A1 is a solution formed by dissolving dibromohydantoin in benzene at a ratio of 5 mmol: 8-10 mL.
4. The low-loss and high-permeability soft ferrite core according to claim 1, characterized in that: The usage ratio of the intermediate product A, 10% palladium carbon and anhydrous ethanol in step A2 is 3g: 0.05-0.09g: 50-55mL.
5. The low-loss and high-permeability soft ferrite core according to claim 1, characterized in that: The usage ratio of the intermediate product B, p-divinylbenzene and anhydrous ether in step A3 is 22-25 mmol: 10 mmol: 80-100 mL.
6. The low-loss and high-permeability soft ferrite core according to claim 1, characterized in that: The usage ratio of the intermediate product C, triethanolamine, anhydrous potassium carbonate and N,N-dimethylformamide in step A4 is 10mmol:60-70mmol:80-90mmol:120-150mL.
7. A method for manufacturing a low-loss and high-permeability soft ferrite core, characterized in that: The following steps are involved: Step 1: Weigh 51-59 parts of Fe2O3, 34-42 parts of MnO, 10-18 parts of ZnO, 0.02-0.07 parts of VO, 0.0012-0.0026 parts of SiO2, 0.03-0.07 parts of CaCO3, 0.1-3.9 parts of performance enhancer and 150-250 parts of anhydrous ethanol according to weight parts, and set aside; Wherein, the performance enhancer is prepared by the following steps: Step A1: stirring nitrobenzene and benzene for reaction, then adding dibromohydantoin solution dropwise while stirring, continuing stirring for reaction after the addition is completed, cooling the reaction product after the reaction is completed, then adding it into distilled water, then extracting it, drying the extract, then vacuum filtering it, and rotary evaporating the filtrate to obtain an intermediate product A; the dosage ratio of the nitrobenzene, benzene and dibromohydantoin solution is 10mmol:30-35mL:20-25mL; the dibromohydantoin solution is a solution formed by dissolving dibromohydantoin in benzene at a ratio of 5mmol:8-10mL; Step A2: adding intermediate product A, 10% palladium carbon and anhydrous ethanol into a three-necked flask, introducing hydrogen to react with stirring, cooling the reaction product after the reaction is completed, and then vacuum filtering, extracting the filtrate, and rotary evaporating the extract to obtain intermediate product B; the amount ratio of the intermediate product A, 10% palladium carbon and anhydrous ethanol is 3g: 0.05-0.09g: 50-55mL; Step A3: stirring the intermediate product B, p-divinylbenzene and anhydrous ether for reaction, cooling the reaction product after the reaction, and then rotary evaporating and recrystallizing to obtain an intermediate product C; the amount ratio of the intermediate product B, p-divinylbenzene and anhydrous ether is 22-25mmol:10mmol:80-100mL; Step A4: stirring the intermediate product C, triethanolamine, anhydrous potassium carbonate and N,N-dimethylformamide for reaction, cooling the reaction product after the reaction, then pouring it into distilled water, then standing it, rotary evaporating the organic phase, and then recrystallizing it to obtain a performance enhancer; the amount ratio of the intermediate product C, triethanolamine, anhydrous potassium carbonate and N,N-dimethylformamide is 10mmol:60-70mmol:80-90mmol:120-150mL; Step 2: Add Fe2O3, MnO, ZnO, VO, SiO2, CaCO3, performance enhancer and anhydrous ethanol into a ball mill for ball milling to obtain ball milling slurry; Step 3: placing the ball mill slurry in a vacuum drying oven to dry, then crushing and sieving, and then adding it to a press to press and form, to obtain a magnetic core green body; Step 4: Place the core green body in a tubular furnace for sintering, then cool it with the furnace, and after grinding and cleaning to remove surface impurities and burrs, a low-loss and high-permeability soft ferrite core is obtained.
8. The method for manufacturing a low-loss and high-permeability soft ferrite core according to claim 7, characterized in that: The ball milling conditions in step 2 are as follows: the ball milling rate is 400-500 r / min, and the ball milling time is 10-20 h.
9. The method for manufacturing a low-loss and high-permeability soft ferrite core according to claim 7, characterized in that: The drying conditions in step three are as follows: temperature is 60-80°C, and drying time is 3-5h; the pressing conditions are pressing pressure of 200-300MPa.
10. The method for manufacturing a low-loss and high-permeability soft ferrite core according to claim 7, characterized in that: The sintering conditions in step 4 are as follows: air environment, sintering temperature of 800-1200° C., and sintering time of 3-5 h.
Citation Information
Patent Citations
Wide-temperature-range low-power-consumption soft-magnetic ferrite material and preparation method therefor
CN105110781A
Preparation method for soft magnetic ferrite with high saturation magnetic induction strength, wide temperature range and low loss
CN105174934A